Preoperative and Postoperative L‐Lactatemia Assessment for the Prognosis of Right Abomasal Disorders in Dairy Cattle - Buczinski, S. (J Vet Intern Med, 2014)
BACKGROUND: Preoperative L‐lactatemia and heart rate have been suggested as prognostic indicators of outcome for cows with right dilatation of the abomasum or volvulus (RDA/AV). However, postoperative L‐lactatemia has not been assessed as a potential prognostic tool. OBJECTIVES: To determine the prognostic value of postoperative L‐lactatemia (LAC (2)), duration of treatment (Dt), relative L‐lactatemia difference (compared with preoperative L‐lactatemia [LAC(1)]) ([LAC(2) − LAC(1)]/LAC(2)) and change in L‐lactate over time ([LAC(2) − LAC(1)]/Dt) as compared to preoperative findings (LAC (1) and heart rate [HR]) as prognostic factors in dairy cows with RDA/AV. ANIMALS: A total of 41 dairy cows were included: 19 with AV and 22 with RDA; 11 cows had a negative outcome (NO) and 30 cows had a positive outcome (PO) based on telephone follow‐up with owners 30 days after surgery. METHODS: Prospective cohort study. Analysis was performed using logistic regression and comparison of area under the receiver operating characteristics curve (AUC) using nonparametric tests. RESULTS: LAC(1) > 1.4 mmol/L or LAC(2) > 2.2 mmol/L had the same accuracy with sensitivity of 100% (95% CI, 75.1–100%) and specificity of 80% (95% CI, 61.4–92.3%) for predicting NO. The relative L‐lactatemia difference ([LAC(2) − LAC(1)]/LAC(1)) or lactate kinetics ([LAC(2) − LAC(1)]/Dt) were not associated with prognosis. The AUC of the preoperative model (which included HR and lnLAC(1)) was 0.92 (95% CI, 0.83–1.0) and that of the postoperative model (including only lnLAC(2)) was 0.95 (95% CI, 0.88–1.0); these were not significantly different. CONCLUSIONS AND CLINICAL IMPORTANCE: Postoperative L‐lactatemia is helpful to predict outcome in cows with RDA/AV. The short‐term change in blood L‐lactate is not a useful prognostic indicator, at least during the period of time spent on the farm for surgery and treatment.